Thực trạng và giải pháp phát triển năng lực thực hành tiếng Anh cho sinh viên ngành Sư phạm Nghệ thuật trong kỉ nguyên số - Trương, Tố Loan (Tạp chí Giáo dục, 2026)
In the context of digital transformation and deep international integration, English practical competence has become one of the core competencies for students majoring in Art Education. However, in reality, these students still face limitations in applying English to professional activities and occupational communication. This article analyzes the theoretical foundations, evaluates the current situation, and proposes solutions to develop English practical competence for Art Education students in the digital era. The study employs document analysis and synthesis methods combined with observations of actual training practices. The findings contribute to improving the quality of training art teachers to meet the requirements of educational innovation and international integration.